Legionnaires’ Disease: Clinicoradiological Comparison of Sporadic Versus Outbreak Cases - Hafiz Rizwan Talib Hashmi; Lakshmi Saladi; Frances Petersen; Misbahuddin Khaja; Gilda Diaz-Fuentes (Clinical Medicine Insights: Circulatory, Respiratory and Pulmonary Medicine, 2017)
Background: In 2015, New York City experienced the worst outbreak of Legionnaires’ disease in the history of the city. We compare patients seen during the 2015 outbreak with sporadic cases of Legionella during the past 5 years. Methods: We conducted a retrospective chart review of 90 patients with Legionnaires’ disease, including sporadic cases of Legionella infection admitted from 2010 to 2015 (n = 55) and cases admitted during the 2015 outbreak (n = 35). Results: We saw no significant differences between the 2 groups regarding demographics, smoking habits, alcohol intake, underlying medical disease, or residence type. Univariate and multivariate analyses showed that patients with sporadic case of Legionella had a longer stay in the hospital and intensive care unit as well as an increased stay in mechanical ventilation. Short-term mortality, discharge disposition, and most clinical parameters did not differ significantly between the 2 groups. Conclusions: We found no specific clinicoradiological characteristics that could differentiate sporadic from epidemic cases of Legionella . Early recognition and high suspicion for Legionnaires’ disease are critical to provide appropriate treatment. Cluster of cases should increase suspicion for an outbreak.